مقارنة التحليل الستاتيكي-اللاخطي لبناء اطاري مختلط متعدد الطوابق ذو أربطة فولاذية وأربطة ذكية SMA - كوسا ميادة; غريب محمد; الغرير ياسين (Latakia University Journal -Engineering Sciences Series, 2016)
In this paper the effect of the distinctive properties of Shape Memory Alloy (SMA) “the ability to undergo large deformation and restore it after stress removal” has been studied to see to what degree it may affect the structural performance of multi-storey tall buildings. Using ANSYS software, two 3D Finite Element (FE) models are built for a composite multi-storey building (20 story) which is resistant to lateral loads by bracing system. One of them is with steel bracing and the other is with SMA bracing. Both models take into account nonlinear material properties of elements and geometric nonlinearity. The model with SMA material shows improved performance compared with the model of steel bracing in terms of residual deformations and ductile performance. تم في هذه الورقة دراسة أثر استخدام الخصائص الاستثنائية في خلائط ذاكرة الشكل Shape Memory Alloy (SMA)" القدرة على ابداء تشوهات كبيرة واستعادتها لتشوهاتها المتبقية بعد إزالة الاجهادات" على السلوك الإنشائي للأبنية العالية متعددة الطوابق. باستخدام برنامج ANSYS نفذّ نموذجي عناصر محدودة ثلاثي الأبعاد لبناء مختلط متعدد الطوابق (20طابق) مقاوم للقوى الجانبية من خلال نظام عناصر تربيط محيطي، في أحد النموذجين كانت عناصر التربيط فولاذية وفي النموذج الآخر استخدمت عتاصر تربيط من خلائط ذاكرة الشكل، النموذجين يأخدان بعين الاعتبار عدم الخطية في مواد العناصر وعدم الخطية الهندسية. أظهر نموذج البناء المستخدم فيه خلائط ذاكرة الشكل سلوكاً محسناً بالمقارنة مع بناء عناصر التربيط الفولاذية فيما يخص التشوهات المتبيقة والسلوك المطاوع.